2013
DOI: 10.26719/2013.19.7.600
|View full text |Cite
|
Sign up to set email alerts
|

Serological pattern of hepatitis B virus among HBsAg negative blood donors in Alexandria, Egypt

Abstract: This study in Alexandria, Egypt was conducted to investigate the distribution of different hepatitis B virus (HBV) markers in apparently healthy blood donors who were hepatitis B surface antigen (HBsAg) negative, and to determine the major independent risk factors. Evidence of past exposure to HBV was found in 148/508 screened donors (29.1%). The most prevalent marker was anti-HBc in 124/508 donors (24.4%), half of whom (63/124) showed anti-HBc only. Anti-HBs prevalence was 15.9%, combined anti-HBc and antiHBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A more recent study put the associated circulating HBV DNA level at <100 IU/ml [7]. El-Ghitany et al in a study reported that in OBI HBV DNA detection in serum or hepatocytes of HBsAg-negative/anti-HBc (IgG)-positive donors may be with or without other markers [33]. Absence of HBV DNA in isolated anti-HBc-positive blood donors in this study would have implied 0% OBI prevalence based on anti-HBc screening alone.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study put the associated circulating HBV DNA level at <100 IU/ml [7]. El-Ghitany et al in a study reported that in OBI HBV DNA detection in serum or hepatocytes of HBsAg-negative/anti-HBc (IgG)-positive donors may be with or without other markers [33]. Absence of HBV DNA in isolated anti-HBc-positive blood donors in this study would have implied 0% OBI prevalence based on anti-HBc screening alone.…”
Section: Discussionmentioning
confidence: 99%